Prezentace německo-českého umění ve stálých expozicích Národní galerie v Praze - Barbora Pavliš Ficková (Acta Universitatis Carolinae: Philosophica et Historica, 2021)
The aim of this article is to show how the National Gallery presented the German–Czech artists and in which way it interpreted them in its presentation of national modern art. The article points out the issues of the canonisation of Czech modern art and how the politics influenced the art history and why it was so complicated to add the German–Czech artists in the Czech art history even after 1989.